Application of Petrovita Liquid Fertilizer on the Growth and Yield of Shallot Plants (Allium Ascalonicum L.) - Sri Purwanti; Budi Utomo; Joko Sri Mulyono (Universitas Panji Sakti, 2023)
Red onion (Allium ascalonicum L.) is a kitchen spice used almost every day by Indonesian people, not to mention small restaurants to large restaurants. The purpose of this study was to determine the application of Petrovita Liquid Fertilizer to the growth and yield of shallot plants. This research research was conducted in 2019 within six months of the year starting from a method using a randomized block design (RBD) consisting of six doses of Petrovita Liquid Fertilizer, with three replications and two sample plants. Use of Liquid Petrovita at doses Z0 = no fertilizer/control, Z1 = 1 ml/l/plant, Z2 = 2 ml/l/plant, Z3 = 3 ml/l/plant, Z4= 4 ml/l/plant, and Z5 = 5 ml/l/plant. Observations consisted of plant length, number of leaves, fresh weight of plants, the weight of plant tubers, and number of plant tubers. The results showed that the dose of Petrovita Liquid Fertilizer Significantly affected all observation variables, namely plant length, number of leaves, number of bulbs, fresh weight of plants and wet weight of shallot bulbs. The treatment of Petrovita Liquid Fertilizer dose of 5 ml per liter of water showed the highest growth and yield with a yield of 30.16 cm plant length, 46.00 leaves, 68.33 grams of wet plant weight, 49.00 grams of tuber weight, and the number of tubers per plant 10.00 although statistically not significantly different from the Petrovita Fertilizer Liquid fertilizer treatment using a dose of 1 ml per liter of water with a plant length of 29.00 cm, number of leaves 34.83, plant wet weight 58.16 gram, tuber weight per plant 38.56 grams and the number of tubers planted were 8.16.